2019
DOI: 10.1039/c9pp00083f
|View full text |Cite
|
Sign up to set email alerts
|

Polarization- and wavelength-dependent defocused scattering imaging of single gold nanostars with multiple long branches

Abstract: We demonstrate the polarization- and wavelength-dependent defocused scattering properties at the localized surface plasmon resonance (LSPR) wavelengths of singe AuNSs having multiple long branches protruding from their surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…AuNPs with rough geometrical features such as sharp tips and edges, commonly known as 'Raman hot spots', can even improve the Raman signals to the order of up to 10 15 fold, 119 because the spatial connement of the surface plasmons at these 'hot spots' produces a highly concentrated local secondary electromagnetic eld. AuNPs with quite a few different morphologies can provide such 'Raman hot spots', including AuNSt, 31,32,118 AuNPy, 16 AuNCr, 36,120 nanourchins, [121][122][123] AuNBP, 124,125 etc. For example, Harmsen et al demonstrated that an AuNSt-based SERS agent can be used to precisely detect macroscopic malignant lesions and microscopic tumor invasion with high sensitivity in animal models of pancreatic cancer, breast cancer, prostate cancer, and sarcoma, and in one human sarcoma xenogra model.…”
Section: Sers-based Optical Imagingmentioning
confidence: 99%
“…AuNPs with rough geometrical features such as sharp tips and edges, commonly known as 'Raman hot spots', can even improve the Raman signals to the order of up to 10 15 fold, 119 because the spatial connement of the surface plasmons at these 'hot spots' produces a highly concentrated local secondary electromagnetic eld. AuNPs with quite a few different morphologies can provide such 'Raman hot spots', including AuNSt, 31,32,118 AuNPy, 16 AuNCr, 36,120 nanourchins, [121][122][123] AuNBP, 124,125 etc. For example, Harmsen et al demonstrated that an AuNSt-based SERS agent can be used to precisely detect macroscopic malignant lesions and microscopic tumor invasion with high sensitivity in animal models of pancreatic cancer, breast cancer, prostate cancer, and sarcoma, and in one human sarcoma xenogra model.…”
Section: Sers-based Optical Imagingmentioning
confidence: 99%
“…These nanostructure SERS substrates can not only improve the detection limit but also have polarization correlation effects on SERS, especially for anisotropic nanostructures, and they are more sensitive to the direction of polarized light. [21][22][23] The polarization Raman spectra of the nanowire substrate show that the SERS signal of the molecule is the strongest when the polarization direction of the incident light is perpendicular to the long axis of the nanowires, and the SERS signal is the weakest when the polarization direction of the incident light is parallel to the long axis. [24][25][26] The linear metal channel is also sensitive to polarized light.…”
Section: Introductionmentioning
confidence: 99%